IMPLEMENTASI PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) UNTUK MENINGKATKAN DIMENSI BERKEBHINEKAAN GLOBAL PADA PESERTA DIDIK KELAS IV SD NEGERI KARANGANYAR GUNUNG 02 - Erna Listiyaningrum; Mudzanatun; Siti Khuluqul Khasanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Education in Indonesia plays a vital role in shaping the future generation to be intelligent, virtuous, and prepared to face global challenges. One of the key steps to achieve this goal is the implementation of the Merdeka Curriculum, which emphasizes character education through the Profile of Pancasila Students. The dimension of global diversity in the Profile of Pancasila Students focuses on developing students' character to appreciate cultural diversity, both locally and globally. The Culturally Responsive Teaching (CRT) approach is considered effective in strengthening this dimension by linking learning to the cultural backgrounds of students.This study aims to implement the CRT approach to enhance students' understanding of global diversity in class IV at SD Negeri Karanganyar Gunung 02. The method used is qualitative descriptive, with data collection techniques including observation, interviews, and documentation. The results show that the application of the CRT approach in learning, such as introducing legend stories from various regions, literacy activities, and intercultural interactions, can increase students' awareness and attitudes toward diversity. Through this approach, students not only gain academic understanding but also develop tolerance, mutual respect, and adaptability in a diverse society. The study concludes that by implementing the dimension of global diversity in the Profile of Pancasila Students, education at SD Negeri Karanganyar Gunung 02 plays a crucial role in shaping students' character to be inclusive, open to differences, and ready to contribute to the global society.